Pembatalan Merek Terdaftar Yang Memiliki Persamaan Nama Pada Pokoknya - Yehuda Goodlife Nusale; Teng Berlianty; Theresia Louize Pesulima (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: According to Law Number 20 of 2016 Concerning Trademarks and Geographical Indications, Article 21 Paragraph 1 Letters a and c Concerning Trademark Registration Procedures which explains that the application for trademark registration is rejected if the registered trademark belongs to another party or is applied for beforehand by another party for similar goods and/or services and has no distinguishing power, but in practice there are registered brands that have the same name in essence, namely the